Contributing to the Decade of Healthy Aging in the Nordic-Russian Arctic - Emelyanova, Anastasia; Golubeva, Elena (Magyar Gerontológia, 2020)
NCM-funded project and expert network “Indigenous and non-indigenous residents of the Nordic-Russian region: Best practices for equity in healthy ageing” will be introduced. The Arctic population is ageing, albeit at various speed across the regions and to a different degree of “healthiness” and “inequity related to healthy ageing” across the life-course. The aim of the research is to contribute to a multidisciplinary understanding of circumstances and patterns of healthy ageing in the Nordic-Russian Arctic and share examples of new solutions as components to the Arctic member states’ national policies and in accordance with the principles of WHO “Decade of Healthy Ageing 2020–2030”. We will focus on a broad evaluation of opportunities the region can bring in to carry activities, building on the principles of the WHO Global Strategy on Ageing and Health, the United Nations Madrid International Plan of Action on Ageing, and aligned to the timing of the United Nations Agenda 2030 on Sustainable Development and the Sustainable Development Goals (SDGs). We will identify best practices at the regional/community levels among Non- and Indigenous older residents, using comparative approach: 1. How we think, feel and act towards age and ageing, 2.Communities fostering the abilities of older people, 3.Delivering culturally safe and person centred care and health services responsive to older people. The project complements our on-going activities under the UArctic Thematic Network “Health and Well-being in the Arctic” and a “Development of a Think Tank Functions of the Northern Dimension Institute”.